Bakaro Recreation Park In Manokwari Regency – Heritage Architecture - Gabriel Joseph David; Pingkan Peggy Egam; Ingerid L. Moniaga (Pusat Publikasi Nusantara, 2024)
Manokwari Regency's Bakaro Recreation Park is a project with the goal of developing a lively and sustainable recreational area for the locals and tourists. This multipurpose park will combine recreational elements including playgrounds, green areas, walking trails, picnic sites, and lodging areas with the natural beauty of the surrounding landscape. Additionally, the design will include aspects that pay tribute to the region's indigenous traditions, which means it heritage in site. Environmental sustainability is one of the project's main objectives, with an emphasis on eco-friendly landscaping employing local flora and landscape elements. In summary, Bakaro Recreation Park aims to create a treasured place for leisure while representing environmental preservation and community pride by integrating nature, recreation, culture, and sustainability in a harmonic manner